2016
DOI: 10.1080/15384101.2016.1151583
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect ofErythroxylum daphnitesextract is associated with G1cell cycle arrest and apoptosis in oral squamous cell carcinoma

Abstract: Plant-derived molecules showing antineoplastic effects have recently gained increased attention as potential adjuvants to traditional therapies for various cancers. Cerrado biome in Brazil contains high floral biodiversity, but knowledge about the potential therapeutic effects of compounds derived from that flora is still limited. The present study investigated the antineoplastic activity of Erythroxylum daphnites Mart., a Brazilian native plant from Cerrado biome, in the SCC-9 oral squamous cell carcinoma cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…8 ; Table 8 ), which include two acetophenone diglycosides ( 188–189 ) isolated from E. cambodianum [ 72 ], neochlorogenic acid ( 190 ) and protocatechuic acid ( 191 ) extracted from E. lucidum [ 68 ], and scoparon ( 192 ) yielded from E. barbatum [ 76 ]. Additionally, five steroids ( 193–197 ) have been identified in this genus according to the previous studies [ 35 , 44 , 46 48 , 76 , 77 ] (Fig. 8 ; Table 8 ).…”
Section: Chemical Compositionmentioning
confidence: 90%
See 2 more Smart Citations
“…8 ; Table 8 ), which include two acetophenone diglycosides ( 188–189 ) isolated from E. cambodianum [ 72 ], neochlorogenic acid ( 190 ) and protocatechuic acid ( 191 ) extracted from E. lucidum [ 68 ], and scoparon ( 192 ) yielded from E. barbatum [ 76 ]. Additionally, five steroids ( 193–197 ) have been identified in this genus according to the previous studies [ 35 , 44 , 46 48 , 76 , 77 ] (Fig. 8 ; Table 8 ).…”
Section: Chemical Compositionmentioning
confidence: 90%
“…5 ; Table 5 ). Besides, recent studies reported five triterpenes ( 92–96 ) from E. ovalifolium [ 14 ], E. daphnites [ 48 ] or E. macrocalyx [ 49 ]. Interestingly, all the triterpenoids identified in this genus are pentacyclic triterpenes.…”
Section: Chemical Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that tumor cell apoptotic generation is a fundamental therapeutic approach for malignant treatment. [34] Modifications in the cell cycle may increase metabolism and affect viability. [35] Currently, we noticed that SL reduced cyclin-D1, CDK 4, CDK 6, and pRB expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Both the ethanolic and water extract of propolis demonstrated antioxidant and antimicrobial activities and pentacosanoic acid, methyl ester (6) was confirmed in both extracts [87] . Hexacosanoic acid, methyl ester (7) was reported in a plant extract demonstrating anticancer properties [88] .…”
Section: Discussionmentioning
confidence: 99%